The toxicology of Butea superba, Roxb - Pongpanparadon A. (2014)
A study to determine the primary toxicological effects of Red Gwow Kreur (Butea superba, Roxb.) dry powder by micronucleus and dominant lethal tests was undertaken. Aqueous solution of Red Gwow Kreur dry powder in doses of 2, 20, 200 and 1,000 mg/kg/day were fed to male rats for 9 weeks. The results showed that 1,000 mg/kg/day of Red Gwow Kreur solution was significantly more effective in inducing the formation of micronuclei in polychromatic erythrocytes than the control (p<0.01), whereas dominant lethal test indicated that none of the doses had a toxic effect on male reproduction. There were no abnormal changes in the number of implantation sites and the number of dead fetuses produced by females that had mated with Red Gwow Kreur treated males in comparison with the controls. In addition, the Red Gwow Kreur solutions had no effect on the body weights of the treated rats.